INVESTIGATION ON THE EXPERT COMMUNITIES AWARENESS OF THE URBAN RIVER WATER QUALITY, CASE STUDY OF SUGUTAMU RIVER, INDONESIA - Imas Komariah; Toru Matsumoto (Lembaga Penelitian Universitas Pasundan, 2016)
Many rivers in urban areas in Indonesia are commonly used as raw water sources for drinking water purposes. Therefore, the water quality of the rivers needs to be maintained. River restoration program becomes a major priority in improving the water sector and environmental, particularly in big cities in Indonesia. Sugutamu River is one of the main rivers passing through the Depok City, West Province of Indonesia. High population . Stakeholder participations should be considered when implementing a participatory program in river restoration project. This program can be developed by increasing the awareness of the community. One of the most important communities is the ‘expert’ communities. In this research, economists, environmental specialists, river engineers, urban planners are selected as the ‘expert’ community. Questionnaires were distributed to the expert communities to investigate how the respondents concern about the importance of river water quality. The result shows that the awareness of the expert community on river water quality and its improvement is higher than on other aspects.